2011
DOI: 10.3354/ame01470
|View full text |Cite
|
Sign up to set email alerts
|

Importance of bacterivory by pigmented and heterotrophic nanoflagellates during the warm season in a subtropical western Pacific coastal ecosystem

Abstract: We investigated temporal variations in the effects of bacterivory by different sizes of heterotrophic nanoflagellates (HNF) and pigmented nanoflagellates (PNF) during a warm period (May to September) in oligotrophic coastal waters of the subtropical western Pacific. Short-term experiments with fluorescently labeled bacteria (FLB) demonstrated ingestion rates of 0.3 to 5.8 bacteria HNF -1 h -1 by HNF in the size range 3-6 µm -rates that were higher than observed for other sizes of HNF. Rates of ingestion by PNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 63 publications
9
36
0
Order By: Relevance
“…Through cell lysis, bacterial biomass is converted to dissolved organic carbon, hence forcing the food web towards a more regenerative pathway (Wilhelm and Suttle, 1999). Our results substantiate earlier studies suggesting that nanoflagellates play an important role in bacterial carbon transfer to higher levels of the food web at this study site during summer (Tsai et al, 2011). However, bacterial production was not balanced by nanoflagellate grazing and viral lysis between June and August (33-68 % of bacterial production) (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Through cell lysis, bacterial biomass is converted to dissolved organic carbon, hence forcing the food web towards a more regenerative pathway (Wilhelm and Suttle, 1999). Our results substantiate earlier studies suggesting that nanoflagellates play an important role in bacterial carbon transfer to higher levels of the food web at this study site during summer (Tsai et al, 2011). However, bacterial production was not balanced by nanoflagellate grazing and viral lysis between June and August (33-68 % of bacterial production) (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Previous estimates of clearance rates of bacteria have been on the order of 10 −3 µL cell −1 h −1 for < 5 µm nanoflagellates and 10 −2 µL cell −1 h −1 for ciliates (Sherr et al, 1989), However, ciliate numbers are so low (∼ 1 cell mL −1 ) (Chen, 2003), thus resulting in ciliate grazing much lower than nanoflagellate grazing throughout observation period. Furthermore, Tsai et al (2011) also reported that the grazing impact by PNF was 20 times higher than that of ciliates at our study site during summer. Thus, the potential effect of nanoflagellate predation on the removal of picoplankton in our study appears to be substantial.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…At most, they were divided into different cell size categories (Zubkov et al, 2001;Chan et al, 2009;Tsai et al, 2011) while very few studies have attempted to discriminate them by taxonomic affiliation (but see Havskum and Riemann, 1996). This is essentially because of the difficulty of determining the taxonomic identity of tiny organisms and simultaneously estimate their in situ grazing rates.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated a declining gradient in nutrient concentration from the coastal area to offshore (Zhang et al, 2007). The phytoplankton community structure and the interactions between phytoplankton and zooplankton in the ECS have been shown to vary across this nutrient gradient (Chan et al, 2003;Chang et al, 2009;Jiao et al, 2002;Tsai et al, 2011). These studies focused on pico-and nano-phytoplankton rather than microphytoplankton.…”
Section: Sites Descriptionsmentioning
confidence: 99%